Is training in obstetric critical care adequate? An international comparison. (February 2019) - Edwards, Z.; Lucas, D.N.; Gauntlett, R.
Highlights: Obstetric critical care is an emerging discipline. Training requirements in obstetric critical care vary a great deal between individual countries. The UK and European CoBaTrICE Intensive Care Medicine curricula are the most detailed. Curricula often consist only of a short list of diagnoses that may result in critically-ill. The development of comprehensive curricula on this subject will assist with improving the quality of care critically-ill women receive. Abstract: Obstetric critical care is an emerging discipline which cuts across speciality boundaries. We have analysed the training curricula in the three major specialities (obstetrics, anaesthesia and intensive care medicine) likely to be involved in the care of the critically-ill obstetric patient, to assess whether it is adequate to ensure effective training on this subject.